2022
DOI: 10.3389/fonc.2022.753234
|View full text |Cite
|
Sign up to set email alerts
|

An Up-To-Date Investigation Into the Correlation Between Proton Pump Inhibitor Use and the Clinical Efficacy of Immune Checkpoint Inhibitors in Advanced Solid Cancers: A Systematic Review and Meta-Analysis

Abstract: BackgroundAlthough immune checkpoint inhibitors (ICIs) have revolutionized the current anticancer therapies, a considerable proportion of patients are found to hardly benefit from these drugs. Accumulating studies have demonstrated that concomitant proton pump inhibitor (PPI) use may affect the clinical efficacy of ICIs; however, their results are inconsistent. In this study, based on updated evidence, we aimed to perform a meta-analysis to clarify the prognostic significance of PPI use in advanced solid cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
3
14
1
Order By: Relevance
“…Later, in a more recent meta-analysis, Qin et al 53 using data from seven studies reported that PPI therapy shortened the PFS and OS of cancer patients treated with ICIs. Finally, Liu et al 54 in a meta-analysis including 17 studies, observed that PPI therapy for cancer patients receiving ICI shortens the OS, but not PFS. Therefore, despite these meta-analysis, the impact of PPIs on ICI therapy still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in a more recent meta-analysis, Qin et al 53 using data from seven studies reported that PPI therapy shortened the PFS and OS of cancer patients treated with ICIs. Finally, Liu et al 54 in a meta-analysis including 17 studies, observed that PPI therapy for cancer patients receiving ICI shortens the OS, but not PFS. Therefore, despite these meta-analysis, the impact of PPIs on ICI therapy still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also demonstrated that PPI use was significantly correlated with reduced clinical benefits. However, the effect of PPIs differs by cancer type, therapeutic strategy, patient age, sample size, and PPI exposure timeframes [135]. A negative correlation with PPI use was found in NSCLC, urothelial carcinoma, and mixed cohorts with multiple cancer types, whereas prolonged PFS was observed in melanoma patients exposed to PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Six meta-analyses [13][14][15][16][17][18] have investigated the survival impacts of concomitant PPI on the effectiveness of ICI, but their results are contradictory. One [14] demonstrated negligible survival influence of PPI on ICI.…”
Section: Introductionmentioning
confidence: 99%
“…One [14] demonstrated negligible survival influence of PPI on ICI. Another three [15,17,18] alluded that PPI could negatively affect ICI in advanced cancers, while the remaining two syntheses [13,16] implied melanoma patients may derive survival benefits due to lower disease recurrence. Despite these six meta-analyses, there has been little investigation and discussion on the interaction of PPI against ICI and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%